Lower-body power relationships to linear speed, change-of-direction speed, and high-intensity running performance in DI collegiate women`s basketball players - Banda, D. S.; Beitzel, M. M.; Kammerer, J. D.; Salazar, I.; Lockie, R. G. (Journal of Human Kinetics, 2019)
Basketball players need to sprint and change direction, and lower-body power (often measured by jump tests) should contribute. How different jumps relate to linear and change-of-direction (COD) speed, and high-intensity running has not been analyzed in Division I (DI) collegiate women`s basketballers. Twelve players completed the vertical jump (VJ), two-step approach jump (AppJ), and standing broad jump (SBJ). Average (AvgP) and peak power (PeakP), and PeakP: body mass (P:BM) were derived from VJ height; relative SBJ was derived from SBJ distance. Players also completed: 10 m and ¾ court sprints (linear speed), the pro-agility shuttle (COD speed), and the Yo-Yo Intermittent Recovery Test Level 1 (YYIRT1; high-intensity running). Pearson`s correlations (p < 0.05) calculated relationships between the jump and running tests. The AppJ correlated to the ¾ court sprint and pro-agility shuttle (r = -.663 to -.805). AvgP and PeakP correlated to the 10 m sprint, ¾ court sprint, and pro-agility shuttle (r = .589-.766). P:BM and relative SBJ correlated with all running tests (linear and COD speed r = -.620 to -.805; YYIRT1 r = .622.803). The AppJ stresses the stretch-shortening capacities of the legs, and this quality is important for faster linear and COD speed. AvgP and PeakP are influenced by body mass; while larger athletes produce greater power, they also may display slower 10 m sprint and pro-agility shuttle times, and lesser YYIRT1 performance. Strength coaches should ensure players can generate high relative power (i.e. P:BM, relative SBJ) for faster linear and COD speed, and high-intensity running.